The Genetic and Evolutionary Drives behind Primate Color Vision - Carvalho, Livia S.; Pessoa, Daniel M. A.; Mountford, Jessica K.; Davies, Wayne I. L.; Hunt, David M. (Frontiers in Ecology and Evolution, 2017)
Primate color vision is based on two to three cone types in the retina, each expressing a different class of visual pigment, making them the only mammals that possess trichromacy. These pigment classes are the short wavelength-sensitive (SWS1) pigment and the long wavelength-sensitive (LWS) pigment, orthologues of the same pigments found in many other vertebrates, as well as the middle wavelength-sensitive (MWS) pigment, a paralogue to the LWS pigment. Trichromacy was achieved differently in Old World and New World primates. In Old World primates, a duplication of the LWS opsin gene occurred giving rise to a “red-sensitive” or L pigment and a “green-sensitive” or M pigment. Their corresponding L and M genes are adjacent on the X chromosome which, together with their high sequence homology, is the underlying cause for the high frequency of red-green color blindness seen in humans. In New World primates and prosimians, however, the mechanism leading to trichromacy, with one exception, is based on a single polymorphic LWS gene, from which different allelic variants encode pigments with differing spectral peaks. X chromosome inactivation limits expression to just one gene per photoreceptor meaning that trichromacy is only seen in females; while all male are red-green color blind. Despite several leading hypothesis, the reasons for the different evolutionary paths taken by Old and New World primates for trichromacy are still unclear and remain to be confirmed.